PERLAWANAN KAUM BURUH PEREMPUAN - Radia Hafid (Universitas Negeri Gorontalo, 2009)
Opportunity to work overseas is considered as one of alterntives in solving employment problems in Indonesia. On the other hand, the opportunity is often viewed as a lucrative business. Formal sector women workers are a real representation of the women phenomena, which are used us references in discussion womenś autonomy problems and decision making. they are also a real manifestatioan of womenś hidden and public resistance against pressures on them. This writing is based on the results of a number of researches on womenś real experiences and involvement in micro-scale decision making and on the factors that influence their struggle. Both act no 13 on the year of 2003 have already regulated the protection of female. Act no 13 on the year 2003 emphasizes sanction if there is infrigements.